Clinical Characteristics of Inflammatory Bowel Disease in Turkey A Multicenter Epidemiologic Survey - Tozun, Nurdan; Atug, Ozlen; Imeryuz, Nese; Hamzaoglu, Hulya O.; Tiftikci, Arzu; Parlak, Erkan; Yurdaydin, Cihan (Lippincott Williams & Wilkins, 2009)
Aim: To investigate the epidemiologic and clinical characteristics of inflammatory bowel disease (IBD) patients in a large multicenter, countrywide, hospital-based study in Turkey. Materials and Methods: Twelve centers uniformly distributed throughout Turkey reported through a questionnaire the new IBD cases between 2001 and 2003. The incidence of ulcerative colitis (UC) and Crohn's disease (CD) has been reported per 100,000 people. Epidemiologic features and clinical characteristics of both diseases were analyzed. Results: During the study period, 661 patients of UC and 216 patients of CD were identified. The incidence in the referral population was 4.4 100,000 and 2.2/100,000 for UC and CD, respectively. The age of the patients showed the characteristic biphasic distribution with 2 peaks between 20 and 30 and 50 and 70 years. A male predominance was observed in both diseases. A history of smoking was detected in 15.5% of UC patients and 49.3% of patients with CD. Family history was positive in 4.4% in UC and 8.3% in CD patients. Concomitant amebiasis was observed in 17.3% of patients with UC and 13.5 of patients with CD. A history of appendectomy was reported in 15% of patients with CD and only 3% of patients with UC. Both extraintestinal and local complications were more frequent in CD patients, whereas arthritis was most common in both diseases. Conclusions: IBDs are frequently encountered in Turkey. IBD incidence is lower than North and West Europe but close to Middle East in our country. The majority of IBD cases are diagnosed in young people (20 to 40 y) with predominance in males. The rate of both intestinal and extraintestinal complications in our population was low when compared with the data reported in the literature. IBD and especially UC, can coexist with amebiasis or become manifest with amebic infestation. The presence of concomitant ameba may create confusion and cause dilemmas in the diagnosis and treatment of UC.
Keywords: inflammatory bowel disease; ulcerative colitis; Crohn's disease; epidemiology; Turkey